1998
DOI: 10.1182/blood.v91.1.301
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Anemia in Human Immunodeficiency Virus (HIV)-Infected Persons: Results From the Multistate Adult and Adolescent Spectrum of HIV Disease Surveillance Project

Abstract: To study the incidence of, the factors associated with, and the effect on survival of anemia in human immunodeficiency virus (HIV)-infected persons, we analyzed data from the longitudinal medical record reviews of 32,867 HIV-infected persons who received medical care from January 1990 through August 1996 in clinics, hospitals, and private medical practices in nine United States cities. We calculated the 1-year incidence of anemia (a hemoglobin level of <10 g/dL or a physician diagnosis of anemia); the adjus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
228
12
11

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(267 citation statements)
references
References 25 publications
16
228
12
11
Order By: Relevance
“…A weak correlation was found between plasma viral load and haemoglobin levels in a study from Luxembourg (33). It is well established that a lower CD4 cell count is associated with lower haemoglobin levels (1,40).…”
Section: Discussionmentioning
confidence: 95%
“…A weak correlation was found between plasma viral load and haemoglobin levels in a study from Luxembourg (33). It is well established that a lower CD4 cell count is associated with lower haemoglobin levels (1,40).…”
Section: Discussionmentioning
confidence: 95%
“…While excellent weighted all cause mortality indices have been established in HIV infection [3,[11][12][13][14], these have focused on HIV markers (CD4 cell count, HIV RNA and AIDSdefining conditions). They have largely omitted biomarkers of anaemia [15][16][17][18], liver disease [8,[19][20][21], and renal disease [22,23] despite their documented association with both immunodeficiency and survival. In this study we used the Veterans Aging Cohort Study (VACS), a sample of over 13 500 veterans initiating cART within the Veterans Affairs Healthcare System (VA), to develop and initially validate the VACS Index, which combines HIV and 'non-HIV' biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that patients with HIV infection and low haemoglobin (Hb) levels have a higher mortality risk than less anaemic comparison groups, even after controlling for CD4 cell count and viral load [2,[6][7][8]. Low Hb levels have also been shown to be associated with disease progression to AIDS and with unfavourable outcomes of treatment, such as opportunistic infections and neurological deterioration [2].…”
Section: Introductionmentioning
confidence: 99%
“…While ZDV has been shown to be associated with anaemia in studies of patients with HIV infection [5,6,[9][10][11], the risk ratio of anaemia for HAART regimens containing ZDV compared with HAART regimens not containing ZDV has not been rigorously established in a US patient cohort. In this retrospective study of HIVinfected out-patients who were not in clinical trials, we computed the incidence of anaemia among patients treated with ZDV and compared the risk of anaemia during ZDV treatment with that of patients treated with HAART regimens that did not contain ZDV.…”
Section: Introductionmentioning
confidence: 99%